Clinically translatable quantitative molecular photoacoustic imaging with liposome-encapsulated ICG J-aggregates - Cayla A. Wood; Sangheon Han; Chang Soo Kim; Yunfei Wen; Diego R. T. Sampaio; Justin T. Harris; Kimberly A. Homan; Jody L. Swain; Stanislav Y. Emelianov; Anil K. Sood; Jason R. Cook; Konstantin V. Sokolov; et al. (Nature Communications, 2021)
Photoacoustic imaging is limited by a lack of contrast agents which can enable combined molecular and physiological imaging at depth. Here the authors address these limitations by developing and validating a contrast agent based on targeted liposomes loaded with J-aggregated indocyanine green dye.